Immunodeficiency with susceptibility to lymphoma with complex genotype affecting energy metabolism (FBP1, ACAD9) and vesicle trafficking (RAB27A) - Brauer, Nina; Maruta, Yuto; Lisci, Miriam; Strege, Katharina; Oschlies, Ilske; Nakamura, Hikari; Böhm, Svea; Lehmberg, Kai; Brandhoff, Leon; Ehl, Stephan; Parvaneh, Nima; Klapper, Wolfram; et al. (Frontiers in Immunology, 2023)
Inborn errors of immunity (IEI) are characterized by a dysfunction of the immune system leading to increased susceptibility to infections, impaired immune regulation and cancer. We present a unique consanguineous family with a history of Hodgkin lymphoma, impaired EBV control and a late onset hemophagocytic lymphohistiocytosis (HLH). Overall, family members presented with variable impairment of NK cell and cytotoxic T cell degranulation and cytotoxicity. Exome sequencing identified homozygous variants in RAB27A, FBP1 (Fructose-1,6-bisphosphatase 1) and ACAD9 (Acyl-CoA dehydrogenase family member 9). Variants in RAB27A lead to Griscelli syndrome type 2, hypopigmentation and HLH predisposition. Lymphoma is frequently seen in patients with hypomorphic mutations of genes predisposing to HLH. We hypothesize that the variants in FBP1 and ACAD9 might aggravate the clinical and immune phenotype, influence serial killing and lytic granule polarization by CD8 T cells. Understanding of the interplay between the multiple variants identified by whole exome sequencing (WES) is essential for correct interpretation of the immune phenotype and important for critical treatment decisions.